2014
DOI: 10.3174/ajnr.a3876
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Tumor Progression from Pseudoprogression in Patients with Posttreatment Glioblastoma Using Multiparametric Histogram Analysis

Abstract: BACKGROUND AND PURPOSE:The multiparametric imaging can show us different aspects of tumor behavior and may help differentiation of tumor recurrence from treatment related change. Our aim was to differentiate tumor progression from pseudoprogression in patients with glioblastoma by using multiparametric histogram analysis of 2 consecutive MR imaging studies with relative cerebral blood volume and ADC values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 24 publications
1
84
0
Order By: Relevance
“…29 In summary, the rate of confirmed pseudoprogression was low for patients with newly diagnosed glioblastoma treated with bevacizumab plus RT/TMZ and had a negligible effect on the assessment of PFS. We also inferred that pseudoresponse had minimal impact on PFS, based on a lack of differential bias in how tumor progression was confirmed.…”
mentioning
confidence: 84%
“…29 In summary, the rate of confirmed pseudoprogression was low for patients with newly diagnosed glioblastoma treated with bevacizumab plus RT/TMZ and had a negligible effect on the assessment of PFS. We also inferred that pseudoresponse had minimal impact on PFS, based on a lack of differential bias in how tumor progression was confirmed.…”
mentioning
confidence: 84%
“…Accurate identifica-tion of PsP and TP is critical because patients with TP may require a change in therapeutic strategy while those with PsP may not. While published reports have attempted to differentiate PsP from TP, [4][5][6][7] these studies did not account for the common finding of a mixture of treatment-related changes and recurrent tumor. Management of these partial responders may be challenging, with short-interval imaging studies often required to determine clinical course.…”
mentioning
confidence: 99%
“…8,9 Both mean and minimum MD values have been used in differentiating PsP from TP. [4][5][6]10 However, due to the heterogeneity of treatment response, MD may have a limited role because reduced diffusion could represent not only highly cellular tumor areas but also inflammatory processes. 9 DTI is increasingly being used in the characterization of glioblastomas 9,11 ; anisotropy measures, including fractional anisotropy (FA), linear anisotropy (CL), planar anisotropy (CP), and spheric anisotropy (CS), have been used to differentiate glioblastomas from metastasis [11][12][13] and primary cerebral lymphomas.…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] Previous studies found that the fifth percentile of the cumulative ADC histogram based on the entire newly developed or enlarged enhancing lesion could be used to accurately differentiate them. 17,21 Specifically, Chu et al 17 reported a sensitivity of 73% and a specificity of 73% for diagnosing true progression, by using a cutoff ADC value of 929 ϫ 10 Ϫ6 mm 2 /s.…”
Section: Discussionmentioning
confidence: 99%
“…Among the many parameters derived from advanced MR imaging techniques, DWI has been consistently reported to be helpful in differentiating tumor progression from treatment-related changes or necrosis. [15][16][17][18][19][20][21][22] Meanwhile, most previous studies pertaining to the role of conventional MR imaging have not shown promising results. 9,23 Nevertheless, a recent study focusing on the conventional MR imaging findings has proposed subependymal enhancement as a useful MR imaging marker for differentiating true progression from pseudoprogression.…”
mentioning
confidence: 99%